Implementation research in health: a practical guide - and Peters, David; Tran, Nhan; Adam, Taghreed (World Health Organization, 2013)
Interest in implementation research is growing, largely in recognition of the contribution it can make to maximizing the beneficial impact of health interventions. As a relatively new and, until recently, rather neglected field within the health sector, implementation research is something of an unknown quantity for many. There is therefore a need for greater clarity about what exactly implementation research is, and what it can offer. This Guide is designed to provide that clarity. Intended to support those conducting implementation research, those with responsibility for implementing programs, and those who have an interest in both, the Guide provides an introduction to basic implementation research concepts and language, briefly outlines what it involves, and describes the many opportunities that it presents. The main aim of the Guide is to boost implementation research capacity as well as demand for implementation research that is aligned with need, and that is of particular relevance to health systems in low- and middle-income countries (LMICs). Research on implementation requires the engagement of diverse stakeholders and multiple disciplines in order to address the complex implementation challenges they face. For this reason, the Guide is intended for a variety of actors who contribute to and/or are impacted by implementation research. This includes the decision-makers responsible for designing policies and managing programs whose decisions shape implementation and scale-up processes, as well as the practitioners and front-line workers who ultimately implement these decisions along with researchers from different disciplines who bring expertise in systematically collecting and analyzing information to inform implementation questions. The opening chapters (1-4) make the case for why implementation research is important to decision-making. They offer a workable definition of implementation research and illustrate the relevance of research to problems that are often considered to be simply administrative and provide examples of how such problems can be framed as implementation research questions. The early chapters also deal with the conduct of implementation research, emphasizing the importance of collaboration and discussing the role of implementers in the planning and designing of studies, the collection and analysis of data, as well as in the dissemination and use of results. The second half of the Guide (5-7) detail the various methods and study designs that can be used to carry out implementation research, and, using examples, illustrates the application of quantitative, qualitative, and mixed-method designs to answer complex questions related to implementation and scale-up. It offers guidance on conceptualizing an implementation research study from the identification of the problem, development of research questions, identification of implementation outcomes and variables, as well as the selection of the study design and methods while also addressing important questions of rigor.
Keywords: Delivery of Health Care; Health Plan Implementation; Health Policy; Health Services Research; Research Design; standards